MUSIC THERAPY - AN INNOVATION: संगीत चिकित्सा - एक नवाचार - Bohra, Manish (International Journal of Research -GRANTHAALAYAH, 2015)
Music therapy is the only proven and rational form of ancient music method developed in the sequence of human development. The therapeutic and proven proven method of musical elements by professionals to achieve personal goals related to treatment is called music therapy. The fulfillment of physical, psychological, emotional, intellectual, logical and social or community needs within the purview of medical practice can be considered as the purpose of music therapy. Music is known as an element that contributes positively to the development of personality development, communication skills development, creativity and creativity development, expression and cognition abilities. Music from fetus to death affects the entire life cycle. It is a worldwide language that affects everyone in one way or another. मानव विकास क्रम में विकसित प्राचीन संगीत पद्धति का तर्कपूर्ण एवं प्रयोग सिद्ध स्वरूप ही संगीत चिकित्सा है। उपचार संबंधी व्यक्तिगत लक्ष्यों की प्राप्ति हेतु पेशेवरों द्वारा सांगीतिक तत्वों का चिकित्सकीय, प्रमाण सिद्ध प्रयोग विधि एवं प्रक्रिया संगीत चिकित्सा कहलाती है। शारीरिक, मनोवैज्ञानिक, भावनात्मक, बौद्धिक, तार्किक एवं सामाजिक अथवा सामुदायिक आवश्यकताओं को चिकित्सकीय प्रविधि की परिधि में रहकर पूर्ण करना संगीत चिकित्सा का उद्देश्य माना जा सकता है। संगीत एक ऐसे तत्व के रूप में जाना जाता है जो व्यक्तित्व विकास, सम्प्रेषण कौशल विकास, रचनात्मकता एवं सृजनशीलता विकास, अभिव्यक्ति एवं अनुभूति परख योग्यताओं के विकास में सकारात्मक योगदान देता है। भ्रूण से मृत्युपर्यन्त संगीत संपूर्ण जीवन चक्र को प्रभावित करता है यह एक विश्वव्यापी भाषा है जो प्रत्येक को किसी न किसी रूप में प्रभावित करती है।